Efficacy of diagnostic monocular occlusion in revealing the maximum angle of exodeviation. Issue 11 (3rd June 2014) - Han, Jeong Mo; Yang, Hee Kyung; Hwang, Jeong-Min
Abstract : Aims: To determine the efficacy of diagnostic monocular occlusion in revealing the maximum angle of exodeviation compared with repeated measurements taken during three or more consecutive examinations in the outpatient clinic. Methods: We retrospectively analysed 185 patients with intermittent exotropia in an institutional referral centre. The angle of exodeviation was measured at distance and near fixation on three or more consecutive examinations in the outpatient clinic. Then 1 day of diagnostic monocular occlusion was performed and the angle of exodeviation was measured. Results: After diagnostic monocular occlusion, the mean angle of deviation at distance (23.5 prism dioptres (PD)) and near fixation (23.5 PD) was significantly smaller compared with the average maximum angle of deviation before occlusion at distance (27.0 PD) and near fixation (25.2) (p=0.001, 0.022). However, 26 patients (14.1%) showed an increase of ≥5 PD in their distant angle after occlusion and 57 patients (30.8%) showed an increase of ≥5 PD in their near angle of deviation. After occlusion, 39.1% (9/23) of divergence excess (DE)-type, 20.0% (3/15) of convergence insufficiency (CI)-type and 2.7% (4/147) of basic-type exotropia were converted to other types. Patients with hyperopia were more likely to show a significant increase of ≥5 PD during near fixation. Conclusions: Diagnostic monocular occlusion could be useful in patients with DE-type or CI-type exotropia and with hyperopia. In other cases, however, it has a limited role in determining the maximum angle of exodeviation compared with multiple examinations.